2006
DOI: 10.1021/ac0600454
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Preconcentration SDS−PAGE of Proteins in Microchips Using Photopatterned Cross-Linked Polyacrylamide Gels

Abstract: The potential of integration of functions in microfluidic chips is demonstrated by implementing on-chip preconcentration of proteins prior to on-chip protein sizing by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE). Two polymeric elements-a thin (approximately 50 microm) size exclusion membrane for preconcentration and a longer (approximately cm) porous monolith for protein sizing-were fabricated in situ using photopolymerization. Contiguous placement of the two polymeric elements in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
172
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(175 citation statements)
references
References 34 publications
2
172
1
Order By: Relevance
“…We emphasize that this is fundamentally different from the preconcentration mechanism using an electric field through nanochannels, resulting in the enrichment of both co-ions and counterions at the cathodic side of the nanometer-sized aperture. In addition to these charge-based preconcentration schemes, the enrichment of molecules at the entrance of apertures due to size exclusion has been demonstrated ͑Khandurina et al., 1999;Song et al, 2004;Foote et al, 2005;Hatch et al, 2006; Here we focus on charge-based preconcentration using an electric field through a nanochannel, which is connected by two microchannels ͓see Fig. 21͑a͔͒.…”
Section: Preconcentration Of Moleculesmentioning
confidence: 99%
“…We emphasize that this is fundamentally different from the preconcentration mechanism using an electric field through nanochannels, resulting in the enrichment of both co-ions and counterions at the cathodic side of the nanometer-sized aperture. In addition to these charge-based preconcentration schemes, the enrichment of molecules at the entrance of apertures due to size exclusion has been demonstrated ͑Khandurina et al., 1999;Song et al, 2004;Foote et al, 2005;Hatch et al, 2006; Here we focus on charge-based preconcentration using an electric field through a nanochannel, which is connected by two microchannels ͓see Fig. 21͑a͔͒.…”
Section: Preconcentration Of Moleculesmentioning
confidence: 99%
“…The in situ patterning of polyacrylamide gels has been reported for electrophoretic transport systems (Hatch et al, 2006;Herr et al, 2007;Kondapalli et al, 2011), which as well as magnetic beads used as the solid phase to capture antibodies and as carriers of target antigens are inspiring configurations (Inglis et al, 2004;Lien et al, 2008), if could be adapted to non-electrically interfaced transport.…”
Section: Sample Preparationmentioning
confidence: 99%
“…We use an in situ photopolymerized nanoporous membrane (Song et al 2004a, b;Hatch et al 2006) in our integrated glass microfluidic device for the preconcentration step. Song et al (2004a) have shown high concentration factors (four orders of magnitude local concentration) using these nanoporous membranes.…”
Section: Introductionmentioning
confidence: 99%
“…The in situ fabrication technique allows for easy integration with total analysis systems. Our membranes are fabricated in polyacrylamide as it is hydrophilic, biocompatible, and shows minimal non-specific adhesion (Hatch et al 2006). The pore size of acrylamide gels can be easily adjusted by changing the percentage of monomer components (Holmes and Stellwagen 1991a, b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation